STRATEGI KOMUNIKASI PEMASARAN DA STRATEGI KOMUNIKASI PEMASARAN DALAM PROMOSI WISATA KEPULAUAN BELITUNG (Studi Pada Akun Instagram @explorebelitung): Studi pada Akun Instagram @explorebelitung - Pratama, Nico Agung; Yenrizal; Saputra, Sepriadi (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Politik Universitas Islam Negeri Raden Fatah Palembang, 2024)
The @explorebelitung account is one of the Belitung island tourism tour and travel instagram accounts which was created in 2014 and has 52.2 thousand followers on Instagram, this account also has its own travel agent for tourists who are interested in visiting Belitung island and need a tour guide. The purpose of this study was to find out Instagram as a media for promoting tourism in the Belitung Islands in a marketing communication strategy. The research method used is descriptive qualitative. Data collection techniques are by observation, interviews, and documentation. The primary data source of this research is data from the owner of the Instagram account @explorebelitung through interviews. The secondary data sources are journals, websites, books, and personal archives from the @explorebelitung account. The theory used is the 7P marketing mix theory proposed by Philip Kotler and keller in which there are elements in it, namely Product, Price, Place, Promotion, People, Process, Physical Evidence. The results found in this study are Instagram media has succeeded in being a promotional media for Belitung islands tourism which is shown through a marketing communication strategy, it was found that the products are tour and travel packages, land vehicle rentals, marine vehicle rentals, and documentation services. The price is shown at the price with included attached. Place in this case is the Instagram account @explorebelitung itself. And the Promotion process in this account is always conveyed through an Instagram account but only applies to promotions about destinations and education about tourism in the Belitung islands. The people in this study are HR members who are members of the @explorebelitung Instagram account such as admins, tour guides, and documentation photographers.